Mechanical, thermal, and high-temperature tribological properties of Ti–Al–C reinforced NiCrAlY coatings for boiler applications - Panpan Yang; Chen Chen; Jiawen Hu; Yang Yang; Xia Liu; Gobinda Gyawali; Shihong Zhang; Kang Yang (Journal of Materials Research and Technology)
Severe wear from continuous ash erosion and thermal cycling presents a critical threat to the operational safety and service life of coal-fired boilers, leading to frequent maintenance and substantial economic losses. Applying protective coatings has become a convenient and efficient strategy to improve their high-temperature wear resistance. This paper investigates the high-temperature friction and wear performance of Ti–Al–C reinforced NiCrAlY composite coatings at 600 °C, specifically for boiler applications. The coatings were prepared using plasma spraying, with Ti powder, Al powder, and graphite as raw materials. We systematically studied the effects of varying Ti–Al–C phase ratios (0–60 wt%) on microstructure, mechanical properties, and high-temperature tribological behavior of the coatings. The addition of Ti–Al–C to NiCrAlY resulted in a typical layered structure with a uniform and dense microstructure. Notably, the NiCrAlY coating with an optimal 20 wt% Ti–Al–C content demonstrated superior comprehensive performance. This optimized coating exhibited a microhardness of 624.02 HV0.2, representing a 45.86 % increase compared to the pure NiCrAlY coating. Furthermore, it showed significantly improved high-temperature wear resistance, with its wear rate substantially decreased to 11.92 × 10−15 m3/(N·m), (an 85.75 % decrease), and its thermal conductivity improved by 30.35 %. This study, thus, aims to provide a cost-effective strategy to extend the service life of boiler components operating under extreme thermal conditions.